Fungsi dan Ragam Bahasa Indonesia - Farah Dzakirah; Rahma Ashari Hamzah; Alini Shyalina (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
Language is a means of communication used by humans to interact, express ideas, and build social relationships. Indonesian, as both the national and official language, plays a significant role in the lives of the Indonesian people. In addition to serving as a national identity, it functions as a unifying tool for the country's diverse ethnicities, cultures, and regional languages. This study aims to explain the functions of Indonesian as the national and official language, as well as to examine its language varieties based on usage situations, communication media, and fields of application. The research uses a library research method by exploring and analyzing various relevant literature, including academic books, journal articles, conference proceedings, and official documents. The findings indicate that Indonesian has various forms depending on the context and communication situation. These include formal and informal language, spoken and written forms, and variations based on specific fields such as science, law, journalism, and literature. This diversity reflects the flexibility of Indonesian in meeting the communication needs of society. Beyond being a communication tool, Indonesian also plays important social and cultural roles by strengthening social bonds and serving as a medium for preserving and developing national culture.